Optimization of cellulosic biomass analysis - Shearer, Dustin (Kansas State University, 2013)
Ethanol has become an important source of energy for transportation purposes in the U.S. The majority of the feedstock for this ethanol is corn grain. The use of crop residues and perennial grasses has been proposed as an alternative feedstock for ethanol production using cellulosic conversion processes. Commercial scale production of cellulosic ethanol is still on the horizon. In the meantime a wide variety of studies examining both the technical and economic feasibility of cellulosic ethanol production have been conducted. This is the first study that combines both county level cellulosic feedstock production and farmer participation rates to determine the feasibility of supplying it to cellulosic ethanol plants. This research determines the economic feasibility of supplying cellulosic feedstocks to seven potential add-on cellulosic ethanol plants of 25 million gallons per year at seven existing starch ethanol plants in Kansas. The feedstocks considered are corn stover, sorghum stalks, wheat straw, and perennial switchgrass. A mixed integer programing model determines the amount and mix of cellulosic feedstocks that can be delivered to these plants over a range of plant-gate feedstock prices given transportation costs and farm-gate production costs or breakeven prices. The variable costs of shipping are subtracted from the difference between plant-gate price and farm-gate price to find savings to the plant. The objective function of the model minimizes transportation costs which in turn maximizes savings to the plant. The role switchgrass may have as a feedstock given various switchgrass production subsidies is examined. The results indicate the minimum plant-gate price that must be paid to feedstock producers for all plants to have enough cellulosic feedstocks is $75 per dry ton. Switchgrass feedstocks were only a minor portion of biomass supplied and used without a production subsidy. A Biomass Crop Assistance Program payment increased the supply of switchgrass more than other production subsidies.
Keywords: Optimization cellulosic ethanol; Agricultural economics; Alternative Energy (0363); Economics, Agricultural (0503)